Implementation of POAC-Based Educational Management in Improving Learning Quality: A Case Study at SMA Negeri 1 Sabang - Fauzan Putraga Al-Bahri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Educational management effectiveness at the school level remains a critical yet underexplored determinant of learning quality, particularly in decentralized education systems such as Indonesia's, where schools are granted substantial autonomy in planning and resource management. This study aims to examine the implementation of the four educational management functions—planning, organizing, actuating, and controlling (POAC)—at SMA Negeri 1 Sabang, to assess the effectiveness of this implementation, and to identify the contextual factors that support or hinder it. A qualitative case study approach was employed, with data collected through in-depth interviews, non-participant observation, and document analysis involving the principal, vice-principals, teachers, and administrative staff, and analyzed using the interactive model of data condensation, display, and conclusion drawing. The findings reveal that planning and organizing are procedurally well-documented but remain largely top-down, with teacher involvement limited to a consultative role, whereas actuating and controlling are more strongly associated with observable improvements in instructional practice, driven primarily by the principal's personalized leadership and a dual-layer supervisory approach combining scheduled and informal classroom observation. Overall, management implementation was found to be moderately to highly effective, with the majority of planned programs successfully realized, although supervisory follow-up documentation remained inconsistent. Key supporting factors included communicative principal leadership and an active subject-teacher forum (MGMP), while inhibiting factors included limited infrastructure, resistance to change among some senior teachers, and weak parental participation in academic decision-making. These findings suggest that the impact of educational management on learning quality is driven less by administrative procedure and more by the relational and motivational dimensions of leadership practice. This study contributes to the school-based management literature by demonstrating that effectiveness is contingent not merely on the presence of formal management structures, but on the consistency and quality of their enactment in daily school life.